ANALYSIS OF THE FEASIBILITY STUDY OF A SOUVENIR BUSINESS IN KARYAMUKTI VILLAGE, CIANJUR DISTRICT (CASE STUDY AT ADITIYA SOVENIR SOUVENIR SHOP) - Himawati, Ditiya; Nurcahyo, Bagus; Fajriah, Asha Alin (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
This Souvenirs are objects or small items that are usually purchased by someone as a memento of a particular place or event and usually have sentimental value and are often used to remember an important experience in someone’s life. In this writing, the feasibility study is based on several aspects, namely the decline in sales levels during Covid-19 and failure in the marketing system carried out by the Aditiya Sovenir shop. Therefore, a planning stage is needed so that the business to be built has a minimum risk, including the need to conduct a feasibility study which includes legal aspects, market and marketing aspects, technical & technological aspects, economic & social aspects, environmental aspects, financial aspects and management & HR aspects.Contribution in activity is contributes to the Aditiya Sovenir shop. Methode this study of planning stages using the payback period method which can affect the feasibility when the business is run. Based on the results of the business feasibility analysis on the financial aspect of 0.57 in which the payback period of the Aditiya Sovenir souvenir shop business is 5 months and 7 weeks, it can be concluded that this investment is feasible to accept, and for non-financial aspects all aspects are declared to meet the feasibility criteria. Aditiya Souvenir Souvenir Shop deserves to be developed based on legal, market and marketing aspects. aspects with SWOT method analysis. And for financial aspects based on the payback period method calculation.